2009
DOI: 10.48550/arxiv.0909.1897
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Geometric structures modeled on affine hypersurfaces and generalizations of the Einstein Weyl and affine hypersphere equations

Abstract: An affine hypersurface (AH) structure is a pair comprising a conformal structure and a projective structure such that for any torsion-free connection representing the projective structure the completely trace-free part of the covariant derivative of any metric representing the conformal structure is completely symmetric. AH structures simultaneously generalize Weyl structures and abstract the geometric structure determined on a non-degenerate co-oriented hypersurface in flat affine space by its second fundamen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
2
2

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 83 publications
(174 reference statements)
0
14
0
Order By: Relevance
“…in connection with geometric inverse problems, integrable systems and Einstein-Weyl geometry, cf. [5], [8], [9], [13], [15], [23], [26].…”
Section: Introductionmentioning
confidence: 99%
“…in connection with geometric inverse problems, integrable systems and Einstein-Weyl geometry, cf. [5], [8], [9], [13], [15], [23], [26].…”
Section: Introductionmentioning
confidence: 99%
“…In [39,52] it is shown that the cubic isoparametric polynomials satisfy (1.6). That the cubic isoparametric polynomials solve (1.5) was observed in section 7 of [18] and [19], and is also shown in Equation (6.4.15) (see also Proposition 6.11.1 and Corollary 6.11.2) of [39]. In [55] there are identified two classes of Hsiang algebras, called exceptional and mutant, and it is shown that a Hsiang algebra satisfies (1.5) if and only if it is exceptional or mutant.…”
Section: Introductionmentioning
confidence: 73%
“…In one particularly interesting class of examples considered previously by the author in [18] in a context related to affine spheres, some special cases of which are considered in [39] (see further remarks below), the algebra is nonunital (this can always be arranged by considering the retraction along a unit); exact, meaning that its (left) multiplication representation L • : A → End(A) defined by L • (x) = x • y satisfies tr L • (x) = 0 for all x ∈ A (this condition is called harmonic in [39]); and Killing Einstein, meaning that the bilinear form h is a nonzero multiple of the bilinear form τ (x, y) = tr L • (x)L • (y). The last two conditions, exact and Killing Einstein, are equivalent to the requirements that the associated cubic polynomial P be h-harmonic and satisfy…”
Section: Introductionmentioning
confidence: 97%
“…In [30] the author defined a class of geometric structures, called AH (affine hypersurface) structures, which generalize both Weyl structures and the structures induced on a co-oriented non-degenerate immersed hypersurface in flat affine space by its second fundamental form, affine normal and co-normal Gauß map, and defined for these AH structures equations, called Einstein, specializing on the one hand to the usual Einstein Weyl equations and, on the other hand, to the equations for an affine hypersphere. In the present paper these equations are solved on compact orientable surfaces and some aspects of their geometry in this case are described.…”
mentioning
confidence: 99%
“…The specialization to surfaces of the notion of Einstein AH structure defined in [30] says that an AH structure on a surface is Einstein if there vanishes the trace-free symmetric part of the Ricci curvature of its aligned representative ∇, while the scalar trace of its Ricci curvature satisfies the condition (6.1), generalizing the constancy of the scalar curvature of an Einstein metric, and taken by D. Calderbank in [13,14,15] as the definition of a two-dimensional Einstein Weyl structure. Calderbank's point of view in the two-dimensional case was motivating for the definition of Einstein AH equations in general.…”
mentioning
confidence: 99%